2015
DOI: 10.1021/acs.jmedchem.5b00140
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the ATP Binding Site of Fyn Kinase for the Identification of New Inhibitors and Their Evaluation as Potential Agents against Tauopathies and Tumors

Abstract: Fyn is a member of the Src-family of nonreceptor protein-tyrosine kinases. Its abnormal activity has been shown to be related to various human cancers as well as to severe pathologies, such as Alzheimer's and Parkinson's diseases. Herein, a structure-based drug design protocol was employed aimed at identifying novel Fyn inhibitors. Two hits from commercial sources (1, 2) were found active against Fyn with K(i) of about 2 μM, while derivative 4a, derived from our internal library, showed a K(i) of 0.9 μM. A hit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 67 publications
3
21
0
Order By: Relevance
“…In agreement with our data, a lot of recent studies showed that the use of TKIs, especially against Btk, Syk, and Lyn, is a promising new strategy for targeted treatment of B-cell lymphoid malignancies (Robak and Robak, 2012). Furthermore, these data on Jurl-MK1 confirmed our previously results obtained in K562 CML cell line (Tintori et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In agreement with our data, a lot of recent studies showed that the use of TKIs, especially against Btk, Syk, and Lyn, is a promising new strategy for targeted treatment of B-cell lymphoid malignancies (Robak and Robak, 2012). Furthermore, these data on Jurl-MK1 confirmed our previously results obtained in K562 CML cell line (Tintori et al, 2015). …”
Section: Discussionsupporting
confidence: 91%
“…Since we previously observed, by in vitro enzymatic assay, that 4c compound inhibited different Src kinases, in particular Fyn with IC 50 = 0.07 μM (Tintori et al, 2015), we verified the presence of Fyn protein in our HM cell lines. Interestingly, we observed that its expression is higher and variable in all cell lines compared to HD-PBMCs.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…One of the common starting materials in the synthesis of pyrazolo [3,4-d]pyrimidines is 5-amino-4-cyanopyrazoles (Quintela et al 2001;Song et al 2011;Rahmouni et al 2014;Agrebi et al 2014;Tintori et al 2015;Siebeneicher et al 2016). Reaction of these compounds with nitriles under various conditions is reported (Hanefeld et al 1996;Smith et al 2007;Davoodnia et al 2012).…”
Section: Introductionmentioning
confidence: 99%